Mineros chilenos y realidad económico-social en poemas de Carlos Pezoa Véliz (1912), Pablo Neruda (1950) y Pablo de Rokha (1961) - Benoît Santini (Les Cahiers ALHIM)
Chilean poets Carlos Pezoa Véliz, Pablo Neruda and Pablo de Rokha make of Chilean workers, especially mineworkers, essential poetic subjects in their production. These mineworkers reflect profound changes in the Chilean economy. They are individually portrayed, although this does not stop a collective vision of them. Rhythm, vocabulary and the diverse enunciative postures possess a strong denunciatory weight. This is confirmed by the evocation of the saltpeter mines of the northern Pampas, the destructive workplace of the mineworkers who fight against this destruction. These workers are assaulted and hurt, and the poetic discourse of the three authors reconstructs them in order to preserve the memory of these humble and brave people.